Structural evolution of a strip-cast Al alloy sheet processed by continuous equal-channel angular pressing - Lee, JC; Seok, HK; Suh, JY; Han, JH; Chung, YH (SPRINGER, 2002)
Experiments were conducted on strip-cast 1050 Al alloy sheets using an equal-channel angular pressing (ECAP) process to investigate the feasibility of the technique for producing metal strips. The developed process is capable of introducing shear deformation into metal strips in a continuous mode at a relatively fast forming speed of 10 to 50 m/min. The actual shear-flow patterns as a result of the continuous ECAP were demonstrated and compared with those obtained from numerical calculations. The effects of die geometry on the mechanical properties of the strips were investigated. Observations of the microstructural evolution in the equal-channel angular pressed (ECAPed) samples were conducted using transmission electron microscopy (TEM) as a function of oblique angles. The texture evolution was investigated using orientation distribution function (ODF) analysis. A possible application of this process for producing an Al alloy sheet with high formability and low earing was discussed by calculating the Lankford parameter and the planar anisotropy.
Keywords: ULTRAFINE-GRAINED ALUMINUM; MICROSTRUCTURAL CHARACTERISTICS; SHEAR DEFORMATION; MG ALLOY; TEXTURE; SUPERPLASTICITY